Formación docente en el desempeño académico estudiantil en pruebas de estado (2018)
This investigation arises when observing the low results in national academic tests at the school Instituto Educativo Tecnico Industrial in the last years, which has glimpsed that the teachers profile can be one of the factors that affect in these results or another possible factor would be the disposition of the student towards his education as a technical bachelor. This institution is located on the island of San Andrés in northern Colombia, specifically in the Caribbean Sea. Education as a training process that contributes to the skills to improve student learning and thus prepare for higher education and thus to prepare a professional profile that contributes to measurable knowledge in a standardized manner with evidence that in this case would be the knowledge, that punctuate and measure the educational quality, keeping in mind the previous thing in this study some characteristics that influence the results of this test are analyzed. In the first place, it is shown that some teachers do not have the profile according to a specific area since they must fill in hours that they need to comply with their schedule stipulated by the general education law, secondly, the little interest is shown of the learner in his formative process and in continuing with a higher education. This research has an empiricist epistemological approach that allows to emphasize the experience, keeping in mind the learning to produce the perception and the origin of the knowledge, keeping in mind that the human discernment has a limit, all this based on the knowledge taken of the hand with the experience and experimentation. The epistemological approach is contextualized with the positivist paradigm which aims to sustain that the forecast is an explanation of the fact that occurs taking into account scientific knowledge, which is based on statistics, which is a way to quantify, verify and measure a given logic, therefore the research approach is quantitative because it characterizes measuring phenomena, using a cause-effect analysis and using statistics as a tool to make viable or optimize the accuracy of information. Another element that has this approach is the process that implements since it has the goodness of plucking a sequence, a probability, a deduction and the analysis of the reality of the object of study. To conclude it is necessary to show that the educational institution needs to perform periodic test drills, about three times a month to strengthen knowledge and deepen teaching learning, therefore it is necessary to implement teaching-learning process is strong and that this needs to be strengthened conclusively and effectively for an optimal educational quality.